2014
DOI: 10.1161/strokeaha.114.005620
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Process of Care and Outcomes Among Patients Hospitalized With Intracerebral Hemorrhage

Abstract: Background and Purpose— Although racial/ethnic differences in care are pervasive in many areas of medicine, little is known whether intracerebral hemorrhage (ICH) care processes or outcomes differ by race/ethnicity. Methods— We analyzed 123 623 patients with ICH (83 216 white, 22 147 black, 10 519 Hispanic, and 7741 Asian) hospitalized at 1199 Get With The Guidelines-Stroke hospitals between 2003 and 2012. Multivariable logistic regression with generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 39 publications
5
45
0
Order By: Relevance
“…Impaired CSF flow and resultant hydrocephalus is one of the most important mechanisms by which IVH may contribute to morbidity and mortality in ICH. Blacks with ICH/IVH presented at a younger age in our study and in others 3, 6, 7. Similarly, hydrocephalus after ICH with IVH occurs more commonly in younger patients 24.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Impaired CSF flow and resultant hydrocephalus is one of the most important mechanisms by which IVH may contribute to morbidity and mortality in ICH. Blacks with ICH/IVH presented at a younger age in our study and in others 3, 6, 7. Similarly, hydrocephalus after ICH with IVH occurs more commonly in younger patients 24.…”
Section: Discussionsupporting
confidence: 64%
“…ICH incidence rates are especially high among black patients compared to whites 3, 4, 5. In addition, blacks with ICH present at an earlier age than their white counterparts 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the reported mortality rates in these studies vary substantially depending on the originating country, with rather low short-term mortality in Asian countries [16,17] and markedly higher mortality rates up to 70% in studies originating from European countries [7] and the United States [18] . Two possible factors may account for this finding: first, although the incidence of ICH is known to be higher in Asians than in Caucasians, a recent study on racial/ethnic differences in the outcome of ICH patients found lower risk-adjusted, in-hospital mortality for Asian than white patients with ICH [19] . Second, ICU admission criteria in Asian countries may vary considerably from those in Europe/United States, not at least because of the limited access to tertiary care centers in many Asian countries [20] .…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Despite disparities in care, this relationship has also been identified in other conditions including stroke. 36 The reasons for differences in outcome according to race/ethnicity are varied and include factors at the hospital-level (e.g., quality of care) and patient-level (e.g., preferences of care). Our findings are also concordant with prior studies, which suggest that an individual's health is related to the environment in which he or she lives.…”
Section: Discussionmentioning
confidence: 99%